Desenvolvimento de projeto de fôrmas metálicas para aplicação em sistemas estruturais de concreto armado, por meio da modelagem da informação da construção (BIM) - Pankov, Arthur Wirtzbiki (FT - Faculdade de Tecnologia, 2022)
Due to the increase in the financing of housing in Brazil, and the consequent rise of the demand for residential units, many companies in the civil construction sector have opted to use metal formwork to carry out construction of buildings in cast-in-place concrete wall systems, optimizing the constructive processes and reducing the time necessary for the conclusion of the construction work. The work presented consists in the creation of models of parametrized formwork for projects of buildings that use concrete wall systems, applying computer tools that allow the use of the BIM (Building Information Modelling) technology, which provides numerous advantages for the civil construction sector. The models were created by means of shared parameters, taking into consideration the construction necessities and the adaptation of different disciplines presented in the building, such as plumbing and electrical installations. Following the elaboration of the models and adapting the formwork to the building Project, the interoperability of the parameters was applied to the formwork types to ajust them to the architectural Project, and, then, for the conclusion of the work, the formwork assembly plan was presented.